Analisis Kompetensi Tenaga Kependidikan dalam Mendukung Operasional Pendidikan - Julia Astuti; Suparman (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
In the world of education, educators (Gadik) and education personnel (Gapendik) are human resources who play an important role in shaping the character of the nation through the development of personality and desired values. In accordance with its role as an education provider, this profession requires qualifications and competencies in accordance wi th their respective duties and responsibilities. The role of gadik as teaching staff is inseparable from the role of gapendik in supporting educational operational activities. For this reason, competency standards are needed that must be possessed by Gapendik in an educational institution, including personality competency, social competency, technical competency and managerial competency according to their level. Likewise with Pusdiklatjemen as one of the educational institutions within the Badiklat Kemhan environment. The condition of Pusdiklatjemen personnel, both in terms of quantity and quality, currently does not meet the standards for school administrative personnel. The number of gapendik personnel currently only reaches 66% of the 106 people according to the DSPP Pusdiklatjemen Badiklat Kemhan. Some of the personnel have reached and will enter retirement age, the limited number of personnel who have information and technology (IT) qualifications, outsourcing workers, lack of OB (office boy) personnel in caring for and maintaining cleanliness are factors that hinder the implementation of educational operations. The purpose of this study is to analyze the real conditions and efforts that need to be made in order to support educational operational activities at Pusdiklatjemenhan. The method used in this study is descriptive qualitative using data collection methods in the form of observation, interviews, documentation and literature studies involving gadik and gapendik including widyaiswara, students, structural officials, student coordinators, IT teams, cleaning teams and other gapendik.